Glioma‐derived cancer stem cells are hypersensitive to proteasomal inhibition. (19th December 2016) - Yoo, Young Dong; Lee, Dae‐Hee; Cha‐Molstad, Hyunjoo; Kim, Hyungsin; Mun, Su Ran; Ji, Changhoon; Park, Seong Hye; Sung, Ki Sa; Choi, Seung Ah; Hwang, Joonsung; Park, Deric M; Kim, Seung‐Ki; et al.
Abstract: Although proteasome inhibitors (PIs) are used as anticancer drugs to treat various cancers, their relative therapeutic efficacy on stem cells vs. bulk cancers remains unknown. Here, we show that stem cells derived from gliomas, GSCs, are up to 1, 000‐fold more sensitive to PIs (IC50, 27–70 nM) compared with their differentiated controls (IC50, 47 to »100 μM). The stemness of GSCs correlates to increased ubiquitination, whose misregulation readily triggers apoptosis. PI‐induced apoptosis of GSCs is independent of NF‐κB but involves the phosphorylation of c‐Jun N‐terminal kinase as well as the transcriptional activation of endoplasmic reticulum (ER) stress‐associated proapoptotic mediators. In contrast to the general notion that ER stress‐associated apoptosis is signaled by prolonged unfolded protein response (UPR), GSC‐selective apoptosis is instead counteracted by the UPR. ATF3 is a key mediator in GSC‐selective apoptosis. Pharmaceutical uncoupling of the UPR from its downstream apoptosis sensitizes GSCs to PIs in vitro and during tumorigenesis in mice. Thus, a combinational treatment of a PI with an inhibitor of UPR‐coupled apoptosis may enhance targeting of stem cells in gliomas. Synopsis: Although proteasome inhibitors (PIs) are widely used as anticancer drugs, their relative therapeutic efficacy on cancer stem cells remains unknown. This study shows that glioma stem cells (GSCs) are hypersensitive to PIs, providing a new strategy for the targeting of gliomas. Stem cells derived from gliomas (GSCs) are up to 1, 000‐fold more sensitive to proteasome inhibitors as their differentiated controls. Proteasomal inhibition transcriptionally activates a group of UPR‐associated proapoptotic proteins selectively in GSCs. Proteasome inhibitors act synergistically with inhibitors of endoplasmic reticulum‐associated apoptosis in destroying gliomas. Abstract : Although proteasome inhibitors (PIs) are widely used as anticancer drugs, their relative therapeutic efficacy on cancer stem cells remains unknown. This study shows that glioma stem cells (GSCs) are hypersensitive to PIs, providing a new strategy for the targeting of gliomas.